Gaseous Emission Control of a Basic Chrome Sulfate Plant by an Innovative Method to meet Environmental Standard - Chowdhury, BA; Quader, AKMA; Islam, MS; Ahmed, N; Paul, MK (Journal of Chemical Engineering, 2010)
Journal of Chemical Engineering Vol.ChE 23 1995-2005